1989
DOI: 10.1007/bf02441471
|View full text |Cite
|
Sign up to set email alerts
|

Wideband acoustic transmission of human lungs

Abstract: The measurement of sound transmission in human lungs has shown promise to reveal, by noninvasive methods, information about the structure of peripheral airways and lung tissue. The paper gives a detailed explanation of the instrumentation and testing methods developed to measure sound transmission through human lungs and thoracic structures in the 5-20 kHz frequency range and describes in detail experiments comparing the acoustic lung transmission patterns of four different subject groups. The experimental res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…1b: sound travels at low sound frequencies (< 1 kHz) at only 50 m/sec as is characteristic for quasi-homogeneous air-tissue-compound and it travels between 10 kHz and 1 MHz at the speed in compact tissue. Between 1 kHz and 10 kHz sound is not transmitted, similar to the frequency gap already observed by Goncharoff et al [13]. To examine this hypothesis together with some clinical ramifications, ultrasound transmission above 1 kHz was studied in healthy subjects, and in patients suffering from the presence of extra water (pleural effusion) or extra air (pneumothorax following pleural effusion, emphysema) in their thorax.…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…1b: sound travels at low sound frequencies (< 1 kHz) at only 50 m/sec as is characteristic for quasi-homogeneous air-tissue-compound and it travels between 10 kHz and 1 MHz at the speed in compact tissue. Between 1 kHz and 10 kHz sound is not transmitted, similar to the frequency gap already observed by Goncharoff et al [13]. To examine this hypothesis together with some clinical ramifications, ultrasound transmission above 1 kHz was studied in healthy subjects, and in patients suffering from the presence of extra water (pleural effusion) or extra air (pneumothorax following pleural effusion, emphysema) in their thorax.…”
mentioning
confidence: 77%
“…3a) rather than echo [2] or tracheal air sound [13]. The sound was emitted by a transducer on the back and detected at the sternum at the height of the heart (• ▶ Fig.…”
Section: Healthy Subjects: Initial Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another group have registered slower waves in 10-19 kHz band with speeds from 50 m/s to 300 m/s [33]. An earlier study of sound transmission between trachea and back in the frequency band 1-20 kHz revealed no transmission between 5 and 12 kHz, but some transmission at 12 kHz [34]. Low frequency ultrasound is suitable for detecting air trapping [35].…”
Section: Forced Vibrationsmentioning
confidence: 99%